Emotional Intelligence in the Context of Personal Dispositions Development of Students - Future Psychologists - Chuyko, Halyna; KOLTUNOVYCH, Tetiana; Chaplak, Yan (Lumen Publishing House, 2023)
The article is connected with a theoretical analysis of the emotional intelligence and empirical studies of the development of emotional intelligence in the context of personal dispositions of students future psychologists (n=84). The following methods were used in the empirical study: EQ test K. Barchard, «Diagnosis of emotional intelligence» (N. Hall), «Questionnaire SVF120» (V. Yanke, G. Erdmann, adaptation N. Vodopjanova), «Methods of diagnosing viability» (S. Muddy, adaptation D. Leontiev), «Oxford Happiness Inventory», «Diagnosis of emotionality» (Suvorov, 1976), «Questionnaire Machiavellianism of the individual». Mathematical data processing and graphical representation of the results were performed using the statistical package SPSS 17.0. It is noted that the real impetus for the emergence of the concept of EI in science were the works of G. Gardner and his theory of multiple intelligences. The basic models of ЕІ and the author’s interpretation of this concept are analyzed, which leads to the conclusion: the integrated understanding of this phenomenon by psychologists is still absent, the main definition of the concept of EI is often a list and description of its components, and the main justification for its importance is a list of those areas of life where the role of EI is most obvious.
Keywords: emotional intelligence; emotionality; happiness; Machiavellianism; vitality